Trends of school mathematics education research in the last decade: A bibliometric analytic review - Nasution, Awal Kurnia Putra; Mandasari, Lola; Harahap, Rosliana (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: This study responds to the limited comprehensive evaluations on research trends in school mathematics education through bibliometric approaches, particularly within the past decade. The main aim is to systematically examine how research in school-level mathematics education has evolved from 2015 to 2024 using bibliometric analysis. Method: Publication data were obtained from the Scopus database, with analyses conducted using VOSviewer and the R-Bibliometrix package. These tools were employed to map out key areas such as scientometrics, patterns of scholarly collaboration, institutional participation, and shifts in research methodology. In total, 3,053 documents containing the keywords “mathematics education” and “school” were included in the analysis. Findings: The results reveal a significant surge in publications since 2020, which coincides with the educational challenges brought about by the COVID-19 pandemic. Research in this field has increasingly emphasized the integration of technology, interdisciplinary STEM perspectives, and applied science. The United States and Indonesia have emerged as leading contributors, underlining their active institutional engagement and influential roles in shaping the global landscape of mathematics education research. Most studies continue to be published as scientific articles. Significance: This study provides a thorough overview of recent developments in school mathematics education research. The insights gained are expected to support educators, researchers, and policymakers in formulating more effective and adaptive strategies for the future of mathematics teaching and learning.